Preliminary safety and efficacy of first-line pertuzumab combined with trastuzumab and taxane therapy for HER2-positive locally recurrent or metastatic breast cancer (PERUSE). (23rd February 2019) - Bachelot, T; Ciruelos, E; Schneeweiss, A; Puglisi, F; Peretz-Yablonski, T; Bondarenko, I; Paluch-Shimon, S; Wardley, A; Merot, J -L; du Toit, Y; Easton, V; Lindegger, N; et al.
Abstract: Background: Pertuzumab combined with trastuzumab and docetaxel is the standard first-line therapy for HER2-positive metastatic breast cancer, based on results from the phase III CLEOPATRA trial. PERUSE was designed to assess the safety and efficacy of investigator-selected taxane with pertuzumab and trastuzumab in this setting. Patients and methods: In the ongoing multicentre single-arm phase IIIb PERUSE study, patients with inoperable HER2-positive advanced breast cancer (locally recurrent/metastatic) (LR/MBC) and no prior systemic therapy for LR/MBC (except endocrine therapy) received docetaxel, paclitaxel or nab-paclitaxel with trastuzumab [8 mg/kg loading dose, then 6 mg/kg every 3 weeks (q3w)] and pertuzumab (840 mg loading dose, then 420 mg q3w) until disease progression or unacceptable toxicity. The primary end point was safety. Secondary end points included overall response rate (ORR) and progression-free survival (PFS). Results: Overall, 1436 patients received at least one treatment dose (initially docetaxel in 775 patients, paclitaxel in 589, nab-paclitaxel in 65; 7 discontinued before starting taxane). Median age was 54 years; 29% had received prior trastuzumab. Median treatment duration was 16 months for pertuzumab and trastuzumab and 4 months for taxane. Compared with docetaxel-containing therapy, paclitaxel-containing therapy was associated with more neuropathy (all-grade peripheral neuropathy 31% versus 16%) but less febrile neutropenia (1% versus 11%) and mucositis (14% versus 25%). At this preliminary analysis (52 months' median follow-up), median PFS was 20.6 [95% confidence interval (CI) 18.9–22.7] months overall (19.6, 23.0 and 18.1 months with docetaxel, paclitaxel and nab-paclitaxel, respectively). ORR was 80% (95% CI 78%–82%) overall (docetaxel 79%, paclitaxel 83%, nab-paclitaxel 77%). Conclusions: Preliminary findings from PERUSE suggest that the safety and efficacy of first-line pertuzumab, trastuzumab and taxane for HER2-positive LR/MBC are consistent with results from CLEOPATRA. Paclitaxel appears to be a valid alternative taxane backbone to docetaxel, offering similar PFS and ORR with a predictable safety profile. ClinicalTrials.gov: NCT01572038.